Experience capitalization: Practice what you preach... But what to preach? And how to practice? - Lepage, Marc (Technical Centre for Agricultural and Rural Cooperation, 2019)
My job is to make sure that we learn from what we already know. It sounds easy, but it's not as straightforward as one thinks.